Narratives need not end well; nor say it all. (8th May 2023) - Andreetta, Sara; Spalla, Davide; Treves, Alessandro
Abstract: To fully embrace situations of radical uncertainty, we argue that the theory should abandon the requirements that narratives, in general, must lead to affective evaluation, and that they have to explain (and potentially simulate ) all or even the bulk of the current decisional context. Evidence from studies of incidental learning show that narrative schemata can bias decisions while remaining fragmentary, insufficient for prediction, and devoid of utility values.